2018
DOI: 10.2147/tcrm.s150049
|View full text |Cite
|
Sign up to set email alerts
|

Meconium-stained amniotic fluid: a risk factor for postpartum hemorrhage

Abstract: Background/aimClinical data with respect to the impact of meconium on the risk of maternal hemorrhage are scarce. Therefore, in this study, we aimed to determine whether meconium-stained amniotic fluid (MSAF) represents a risk factor for postpartum hemorrhage (PPH) after vaginal delivery in a large unselected population.Patients and methodsA retrospective cohort study evaluated 78,542 consecutive women who had a vaginal delivery between 24th and 44th weeks of gestation. The women who had undergone cesarean sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…The rate of meconium‐stained amniotic fluid was higher in the amnioinfusion group compared with the control group. Meconium‐stained amniotic fluid is considered a marker of fetal distress 23 and has been associated with increased risk of various adverse maternal and neonatal outcomes including non‐reassuring fetal heart rate, cesarean delivery, postpartum hemorrhage, low Apgar scores, and meconium aspiration syndrome 24,25 . As no differences in the rate of maternal or neonatal complications were found, the results from the present study further strengthen the assumption that amnioinfusion after diagnosis of SII is safe.…”
Section: Discussionsupporting
confidence: 78%
“…The rate of meconium‐stained amniotic fluid was higher in the amnioinfusion group compared with the control group. Meconium‐stained amniotic fluid is considered a marker of fetal distress 23 and has been associated with increased risk of various adverse maternal and neonatal outcomes including non‐reassuring fetal heart rate, cesarean delivery, postpartum hemorrhage, low Apgar scores, and meconium aspiration syndrome 24,25 . As no differences in the rate of maternal or neonatal complications were found, the results from the present study further strengthen the assumption that amnioinfusion after diagnosis of SII is safe.…”
Section: Discussionsupporting
confidence: 78%
“…It stated that meconium stained amniotic fluid is associated with increased risk of postpartum hemorrhage than clear amniotic fluid. 11 In our study no such relation was studied. A study conducted in Switzerland also stated increased incidence of PPH in recent years and associated with decreased tone of uterus which is its main cause.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, our results showed that in women with thick MSAF in the first stage of labor, the 24-hour vaginal bleeding volume was greater than that in women with thin MSAF, but the rate of PPH was not significantly different (data not shown). Previously published literature revealed that MSAF is significantly associated with a higher risk of moderate (1000–2000 mL) and severe (>2000 mL) PPH than clear AF, 18 but another study reported the risk is higher for minor (500–1000 mL) and moderate but not for severe PPH, 19 a finding which may need further studies. Regarding puerperal infections, our results showed only a slight change in WBC count, CRP and neutrophil percentage or count, and no cases of puerperal infection or death existed in our data, which may be due to the use of antibiotics.…”
Section: Discussionmentioning
confidence: 92%